Heuristics for Integrated Interaction (HII): A New Heuristic Evaluation Technique to Identify Usability Problems in HInt Devices - Barauna, Nasthya; Lima, Márcia; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15080, 2025)
Background: The complexity of Human-Computer Integration (HInt) devices poses challenges for traditional usability assessment methods, as they involve elements that go beyond the interface, demanding new forms of evaluation. These technologies work in symbiosis with the human body and operate autonomously with the user in real time, requiring specific methods that can identify potential failures. Aims: This article introduces the Heuristics for Integrated Interaction (HII) technique, designed to identify usability problems in HInt technologies by using criteria tailored to the integration paradigm. Method: The technique was developed based on a literature review, followed by an empirical study with experts. The experts applied HII to assess a real-world system, reporting their perceptions about its applicability and effectiveness. Results: The results indicated that HII allowed the identification of specific failures not captured by traditional approaches. Participants considered HII’s relevance for integrative contexts and suggested structural and linguistic improvements. Conclusions: The results reinforce the prediction of the technique as an innovative instrument for usability evaluation in HInt devices, thereby contributing to the improvement of the software quality of these systems.